Sihir Dalam Al-Qur???an: Kajian Tafsir Tematik - Niswatul Malihah; Tapa???ul Habdin (Program Studi Ilmu Al-Qur'an dan Tafsir, 2022)
This research examines magic in holy Qur???an, which the magic is a maksiat and a great sin, because magic is an odd thing that seems to be an an extraordinary thing but not extraordinary. It can be including to be great sins category because magic can be learned and obtained through with demon approach by committing crimes of statement which contains destruction and praise to demon. Look at the rise if shamanic practices right now, it???s often found that people who depend on witchcraft in their view can give the benefit for him and other, even the magic essentially brings to mudharat. This phenomenon can be looked from peoples whom come to shamans as alternative medicine or to aim of predicting their future or to harm other with guna-guna because of desire and envy. In this regard, Al-Qur???an has explained how dangerous the magic, and need to necessary to understand how the nature of magic, the relationship with demon and mudharat in life. The researcher explains with the thematic interpretation with library research. This research uses primary data sources is Al-Qur???an and tafsir books as secondary data sources. The results of the research obtained that magic is real and affect someone???s soul because Al-Qur???an has explained the verses relating to the magic which happened on the prophet???s time and will not inflict to mudharat from magic to His creatures except His permission. Based of law, the magic is a prohibited act in Al-Qur???an for learn or teach it and the perpetrator of magic is punished as kafir because there is an element of devil worship on it.